The sporting sanctions against russia: debunking the myth of sport's neutrality - Goretti, L. (IAI Papers, 2022)
In response to Russia`s aggression against Ukraine, the International Olympic Committee and international sports federations took a number of exceptional measures: among them, the exclusion of Russian and Belarusian athletes from most international sports competitions and a ban on organising events on Russian territory. These measures were officially framed not as sanctions, but rather as a way to defend the neutrality of the sporting domain. In reality, they were the result of pressures from Western governments, public opinions, sports organisations and athletes, and highlighted the constitutive entanglement between international sport and international politics at both the organisational and symbolic level. Setting an important precedent, the sanctions against Russia may carry significant implications for the governance of international sport in the future, potentially leading to greater attention to humanitarian and human rights considerations, but also to increased fragmentation.